2011
DOI: 10.1007/s00380-010-0111-3
|View full text |Cite
|
Sign up to set email alerts
|

In patients with idiopathic venous thrombosis, interleukin-10 is decreased and related to endothelial dysfunction

Abstract: The aim of this study was to evaluate the levels of anti-inflammatory interleukin-10 and pro-inflammatory cytokines and their relationship to endothelial function in patients with idiopathic venous thrombosis. Forty-nine eligible patients of both sexes with idiopathic venous thrombosis and 48 matched control subjects were studied. Levels of inflammatory markers were determined. Endothelial function was evaluated by ultrasound measurement of the flow mediated dilatation (FMD) of the brachial artery. Compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 26 publications
2
27
1
1
Order By: Relevance
“…For instance, while some studies, including those with prospective design, demonstrated a significant effect of inflammation, as reflected by increased CRP levels, on the risk of VTE, [19][20][21] others found no link between CRP and a future event of VTE. [22][23][24][25] Previously, we have shown in a case-control study that IL-6 levels were significantly associated with VTE, 26 which agreed with some, [27][28][29] but not all, studies including a prospective cohort. 30,31 Taking into account the close relationship between abdominal obesity and inflammation and the potential role of these conditions in the development of VTE, we have sought to extend our investigation by exploring whether inflammation could contribute to the thrombosis risk from abdominal obesity.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…For instance, while some studies, including those with prospective design, demonstrated a significant effect of inflammation, as reflected by increased CRP levels, on the risk of VTE, [19][20][21] others found no link between CRP and a future event of VTE. [22][23][24][25] Previously, we have shown in a case-control study that IL-6 levels were significantly associated with VTE, 26 which agreed with some, [27][28][29] but not all, studies including a prospective cohort. 30,31 Taking into account the close relationship between abdominal obesity and inflammation and the potential role of these conditions in the development of VTE, we have sought to extend our investigation by exploring whether inflammation could contribute to the thrombosis risk from abdominal obesity.…”
Section: Introductionsupporting
confidence: 69%
“…For instance, although in vitro studies show that CRP and IL-6 are capable of increasing the expression of TF, 35,36 the key inducer of blood coagulation, clinical data on the association of these inflammatory markers with venous thrombotic disease are conflicting and, particularly for IL-6, also limited. Whereas some studies demonstrated that IL-6 is associated with VTE, [27][28][29] others, including a prospective cohort, found no relationship. 30,31 For CRP, there is strong evidence that this acute-phase protein is a predictor of arterial thrombotic events.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, previous case-control studies have shown that serum/plasma levels of soluble adhesion molecules derived from immunocompetent or endothelial cells (P-selectin, VCAM-1 and intercellular adhesion molecule 1 (ICAM-1), various proinflammatory cytokines (Interleukin(IL)1-β, IL-6, CXCL-8 (IL-8), IL-10, CCL-2) and tumor necrosis factor α (TNFα) as well as matrix metalloprotease (MMP)-9 are altered in DVT patients [11][12][13][16][17][18] compared with healthy controls [19]. These soluble mediators form a dynamic and interactive network, and it may therefore be more relevant to investigate broader mediator plasma profiles rather than the levels of single mediators.…”
Section: Introductionmentioning
confidence: 99%
“…AECOPD and PE are associated with a wide range of inflammatory cells, mediators and cytokine network components, including P-selectin (11,12), inflammatory cytokines (13,14) and leucocytes (15,16). Previous studies have indicated that eosinophilic airway inflammation is also associated with the development of severe AECOPD (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%